Performance-enhancing substances: Is your adolescent patient using? - Holland-Hall, C. (Pediatric Clinics of North America, 2007)
Small, but significant, numbers of adolescents use anabolic-androgenic steroids to improve their appearance or sports performance. Many more use creatine and other performance-enhancing substances with the hope of achieving these goals. This article assists primary care physicians in the office assessment of adolescents who may be using these substances, focusing on identifying adolescents at risk, asking the right questions, and helping adolescents feel comfortable discussing this sensitive topic. Providers must present themselves as credible sources of information on the topic to communicate effectively with adolescent athletes.